2010
DOI: 10.1158/1940-6207.capr-10-0128
|View full text |Cite
|
Sign up to set email alerts
|

A Panel of Sputum-Based Genomic Marker for Early Detection of Lung Cancer

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer death. Early detection of NSCLC will improve its outcome. We previously identified genetic signatures whose genomic copy number aberrations were associated with early stage NSCLC. Here, we aimed to develop a panel of genes that could be detected in sputum for NSCLC early detection. We first optimized a panel of genes by using an in situ minichip for measuring changes of the signatures in sputum of a case-control cohort of 49 NSCLC patients, 49 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 21 publications
(57 reference statements)
0
43
0
Order By: Relevance
“…Sputum was collected from the participants as described in our previous reports 10, 11, 18-23 . Immediately after sputum sample was received, sputum supernatant was prepared as previously described 24 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sputum was collected from the participants as described in our previous reports 10, 11, 18-23 . Immediately after sputum sample was received, sputum supernatant was prepared as previously described 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that molecular genetic changes in the exfoliated respiratory epithelial cells of sputum could provide potential biomarkers for early stage lung cancer 56, 7, 8, 9, 10, 11 . The exfoliated epithelial cells in sputum mainly comprise 1), bronchial epitheliums that are derived from centrally located tumors that mainly are SCC, 2), respiratory epitheliums that may share clonally molecular genetic lesions with SCC tumors , however not directly shed from the primary SCC tumors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection of atypical cells in sputum cells prepared for cytologic examination for the screening of lung cancer is a proven method, but suffers from low sensitivity. The addition of genomic markers can raise the sensitivity of cancer detection to 86% and specificity to 93% (Jiang, 2010). When it comes to actual tumors, interobserver agreement has had a history of similar problems with at best, modest reproducibility.…”
Section: Achieving Personalized Medicine Through Improved Diagnosticsmentioning
confidence: 99%